Dynamic Sectorization - Conceptualization and Application - Sousa, Filipe Soares; Ozturk, Elif Goksu; Lima, Maria Margarida; Nunes, Ana Catarina; Lopes, Isabel Cristina; Oliveira, Cristina Teles; Rodrigues, Ana Maria; Ferreira, José Soeiro (IO 2021 - XXI Congresso da Associação Portuguesa de Investigação Operacional, 2021)
Sectorization is the division of a large area, territory or network into smaller parts considering one or more objectives, intending to optimize or simplify a problem. Dynamic sectorization deals with situations where it is convenient to discretize the time horizon in a certain number of periods. Certainly, the decisions will not be isolated, but they will consider the past and the forthcoming periods. The application areas are diverse and increasing due to the uncertain times in which we live. For example, solving this problem can be useful for delivery companies where the demand is always changing. We propose a conceptualization of dynamic sectorization and apply it to a problem under research related to distribution with variable demand. Furthermore, the solution to that problem is obtained using a Decision Support System developed by the authors.